Legal Politics and Protection of Health Workers in Handling Outbreaks: An Analysis of Incentive Policies and Occupational Safety Guarantees in Indonesia - Riyanto, Ontran Sumantri (CV. Era Digital Nusantara, 2025)
This study investigates how government legal policy shaped incentive schemes and occupational safety guarantees for health professionals during the COVID-19 response in Indonesia. Using a qualitative method with normative legal analysis, the research examines key instruments such as Presidential Decree No. 11 of 2020, Government Regulation instead of Law (Perppu) No. 1 of 2020 (later ratified as Law No. 2 of 2020), Minister of Health Decree No. HK.01.07/MENKES/4239/2021, and Law No. 17 of 2023 concerning Health. The findings reveal that emergency legal policies, which relied heavily on executive discretion, became the foundation for determining incentive mechanisms. Implementation, however, was often hindered by bureaucratic complexity and unequal distribution across regions. Regarding occupational safety, integrating Occupational Safety and Health (K3) principles marked a necessary legal adaptation. Yet, significant shortcomings persisted, most notably in mental health protection and the provision of Personal Protective Equipment (PPE). Psychological support for frontline workers remained underdeveloped, leaving them exposed to burnout and trauma, while PPE shortages and uneven allocation undermined workplace safety. These results demonstrate that legal responses prioritized rapid financial relief but lacked balance with long-term, comprehensive protection. By highlighting this gap, the study contributes to understanding the relationship between political power, the legal framework, and the welfare of health professionals. The implications stress the need for a holistic and integrated legal policy, supported by sustained commitment and adequate resources, to ensure equitable and lasting protection for health professionals in future public health crises.